Drivers of density for the exploited giant clam Tridacna maxima: a meta‐analysis. Issue 3 (7th September 2015) - Van Wynsberge, Simon; Andréfouët, Serge; Gaertner‐Mazouni, Nabila; Wabnitz, Colette C C; Gilbert, Antoine; Remoissenet, Georges; Payri, Claude; Fauvelot, Cécile
Abstract: Giant clam populations have been over‐exploited throughout their range over the past decades for their meat and shells. Tridacna maxima, commonly known as the 'small giant clam', has remained relatively untargeted by fishers in areas where larger species occur (e.g. Tridacna squamosa ), and high densities of the species are still observed on some isolated and enclosed reefs of the Central Pacific. However, it is unclear whether reported discrepancies in densities worldwide reflect differences in fishing pressure only or a combination of differences in exploitation levels and environmental forcing. We reviewed T. maxima surveys throughout its range to (i) identify patterns of density at global scale, site scale (e.g. island) and intrasite scale; (ii) discuss the influence of sampling method on density estimates; and (iii) identify the primary drivers of giant clam density along gradients of human pressure and natural forcing. We found 59 studies that reported density estimates for 172 sites across 26 countries in the Indo‐Pacific and Red Sea. At intrasite scale, densities were strongly dependent on sampling protocols and surveyed habitats. At site scale, we found close links between T. maxima density and human population per reef area, suggesting that isolated reefs where exploitation only recently started may be more vulnerable to stock collapse in the future. Density patterns were also found to vary significantly depending on reef type (e.g. atoll, island, continental coastline). We discuss how natural processes and fishing pressure may control population dynamics and densities among sites, and make recommendations for future research.